Water-based modified composite nano plugging agent and preparation method thereof

By using modified composite nanosealing agents that coat silica with nanoferrous particles in water-based drilling fluid and graft phenyl polyamine, the existing sealing agents have poor dispersion and low salt resistance in high temperature and high salt environments, achieving more efficient sealing effect and more stable dispersion.

CN119614162APending Publication Date: 2025-03-14JINAN YAGE NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411889294.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The sealing agent in existing water-based drilling fluid has poor dispersion in high temperature and high salt environments, low salt resistance and sealing efficiency, and cannot effectively seal the fine nano gaps in the formation.

Method used

Using nano-iron particles as the core, coated silica, and grafted phenyl polyamine long chains on silica, to prepare a modified composite nano-sealing agent. The sealing agent has a small particle size and uniform distribution, with high adsorption properties and salt resistance.

Benefits of technology

It improves the high temperature resistance and dispersion of the sealing agent, enhances the sealing ability of small gaps, improves the sealing efficiency and salt resistance, and reduces the leakage of drilling fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614162A_ABST
    Figure CN119614162A_ABST
Patent Text Reader

Abstract

The invention discloses a water-based modified composite nano plugging agent and a preparation method thereof, and belongs to the technical field of oil field drilling. Adding a surfactant and an emulsifier into an organic solvent to obtain an emulsion, slowly dropwise adding the nano-iron solution into the emulsion, heating and stirring for reaction to obtain an iron-based nano-emulsion; adding nano silicon dioxide into the iron-based nano emulsion, performing ultrasonic treatment, stirring, centrifuging and drying to obtain composite nano particles; and dispersing the composite nanoparticles and a silane coupling agent in an organic solvent, adding polyaminobenzene, alkyl polyaldehyde and formic acid, carrying out a heating reflux reaction in a protective atmosphere, then adding polyaminoalkane, continuing the reflux reaction, spin-drying a reaction solution, and sequentially washing, filtering and drying to obtain the modified composite nano plugging agent. The plugging agent is small in particle size, uniform in distribution, capable of plugging small gaps, good in soil adsorbability, high in salt-resistant stability, capable of adapting to various drilling fluids, free of leakage of the drilling fluids and capable of improving the plugging efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield drilling, and in particular to a water-based modified composite nano plugging agent and a preparation method thereof. Background Art

[0002] In the process of modern oil and gas extraction, along with the enhancement of environmental protection awareness, compared with traditional oil-based drilling fluids, water-based drilling fluids that are water-based, free of toxic and corrosive components, and safer for the environment and workers are used more frequently, and the application of water-based high-efficiency plugging agents that match them is becoming more and more widespread. During the drilling process, after the plugging agent is added to the drilling fluid, it enters the tiny pores of the well wall formation (rock) to form an efficient plugging to reduce rock permeability, reduce liquid intrusion, increase well wall stability, and protect oil and gas reservoirs. Effective plugging can reduce the loss of various chemical components in the drilling fluid, ensure the safety of groundwater and soil, significantly reduce the risk of environmental pollution, and effectively protect oil and gas reservoirs and improve oil and gas recovery.

[0003] Compared with traditional oil-based drilling fluids, water-based drilling fluids have higher requirements for the functional ingredients that go with them. Therefore, the salt resistance, temperature resistance, water phase dispersion stability and plugging properties of plugging agents have become key indicators for measuring high-efficiency plugging agents. The stability and plugging performance indicators of plugging agents are closely related to their physical and chemical indicators such as chemical structure and particle size parameters. Therefore, in recent years, the development of environmentally friendly water-based drilling fluids and their effective components has gradually become an industry consensus. Because silica has high temperature resistance, the research on modified nano-plugging agents has become a hot topic in the industry. The modified silica plugging agents currently used in oil fields are generally grafted with silica or mesoporous silica and polyamines. For example, the patent of application number CN202210082547.5 discloses a strong adsorption anti-salt plugging agent and water-based drilling fluid based on nano-silica, using nano-silica, amino-containing silane coupling agent, D-alanine methyl ester hydrochloride, double-bond chlorinated products and amine compounds containing sulfonic acid functional groups to prepare nano-silica by a step-by-step method, but its particle size distribution is between 146 and 843 nm, and the large particle size leads to a weak migration effect, and it is impossible to plug the fine nano-gaps that account for the majority of the formation pore throats, and the plugging efficiency is low. The patent of application number CN114634802A discloses a heat-resistant and salt-resistant super-hydrophobic coating plugging agent and a preparation method, using tetraethyl orthosilicate, silane coupling agent, alcohol, and alkali to generate nano-silica particles and silane sol, and the silane sol is coated on the nano-silica particles to form a grafted core-shell structure, but the silane sol has poor adsorption performance, and the formed nano-material is also unstable.

[0004] The plugging agent is added to the drilling fluid for use. The mud and water in the drilling fluid contain a large amount of sodium, calcium, magnesium and other ions, which will affect the salt resistance stability of the plugging agent, thereby affecting the plugging performance. In addition, the silica plugging agent has poor dispersibility in the drilling fluid and poor compatibility with the drilling fluid. As the drilling temperature increases, the plugging agent will be stratified in the drilling fluid. Therefore, a stable, small-particle plugging agent is needed that can be more stable in the drilling fluid, prevent the drilling fluid from leaking, and improve the plugging efficiency. Summary of the invention

[0005] In view of the above-mentioned prior art, the purpose of the present invention is to provide a water-based modified composite nano plugging agent and a preparation method thereof. The present invention uses nano iron particles as the core, coated with silicon dioxide, and grafted with long chains of phenyl polyamine on the silicon dioxide to prepare a modified composite nano plugging agent. The plugging agent has a small particle size and uniform distribution, can plug small gaps, has good soil adsorption, high salt resistance and stability, can adapt to various drilling fluids, prevents the drilling fluid from leaking, and improves the plugging efficiency.

[0006] To achieve the above object, the present invention adopts the following technical solution: The first aspect of the present invention provides a method for preparing a water-based modified composite nano plugging agent, comprising the following steps: (1) adding a surfactant and an emulsifier to an organic solvent to obtain an emulsion, dispersing nano iron particles in deionized water to obtain a nano iron solution, slowly dropping the nano iron solution into the emulsion, heating and stirring to react, and obtaining an iron-based nano emulsion; (2) adding nano-silica to the iron-based nano-emulsion, ultrasonicating and stirring, centrifuging and drying to obtain composite nano-particles; (3) The composite nanoparticles and silane coupling agent are dispersed in an organic solvent, polyaminobenzene, alkyl polyaldehyde and formic acid are added, and the mixture is heated to reflux reaction under a protective atmosphere, and then the polyaminoalkane is added to continue the reflux reaction. After the reaction is completed, the reaction solution is spin-dried, and then washed, filtered and dried in sequence to obtain a modified composite nano plugging agent.

[0007] Preferably, in step (1), the surfactant is polyethylene glycol octylphenyl ether, lecithin, cephalin, sodium dodecyl sulfate or sodium stearate; the emulsifier is Tween, Span or inositol phospholipids; the organic solvent is methanol, acetonitrile, ethanol, acetone or glycerol; the nano iron particles are ferroferric oxide, ferric oxide or ferric chloride; and the particle size of the nano iron particles is 10-30 nm.

[0008] More preferably, the surfactant is polyethylene glycol octylphenyl ether, lecithin or sodium stearate; the emulsifier is Tween; the organic solvent is acetonitrile or acetone; and the nano iron particles are ferrosoferric oxide or ferric oxide.

[0009] Preferably, in step (1), the mass ratio of the surfactant, the emulsifier and the organic solvent is 5:2:2; the mass ratio of the nano iron particles to deionized water is 1:5; and the mass ratio of the organic solution to deionized water is 1:2.

[0010] Preferably, in step (1), the heating temperature is 50-100° C.; and the stirring reaction time is 1-3 h.

[0011] More preferably, the heating temperature is 50-80°C.

[0012] Preferably, in step (2), the particle size of the nano-silicon dioxide is 10-200 nm; the mass of the nano-silicon dioxide is 1-20 times the mass of the nano-iron particles; the power of the ultrasound is 10-50 kW; and the stirring time is 1-5 h.

[0013] More preferably, the mass of the nano-silicon dioxide is 1 to 5 times the mass of the nano-iron particles; the power of the ultrasound is 10 to 50 kW; and the stirring time is 1 hour.

[0014] Preferably, in step (3), the mass ratio of silicon dioxide, silane coupling agent and organic solvent contained in the composite nanoparticles is 5:1:25; the molar ratio of polyaminobenzene, polyaminoalkane, alkyl polyaldehyde, formic acid and silicon dioxide contained in the composite nanoparticles is 2:2.1:2.1:10.5:1.

[0015] Preferably, in step (3), the silane coupling agent is selected from KH-590, KH-550, KH-560 or G-570; the organic solvent is selected from toluene, xylene, mesitylene, benzene or biphenyl; the polyaminobenzene is at least one of diphenyl diamine, o-phenylenediamine, 1,5-naphthalenediamine, naphthalene-2,6-diamine, anthracene-1,5-diamine, benzene-1,2,3-triamine or 2,4,6-quinazoline triamine; the alkyl polyaldehyde is a polyalkyl dialdehyde, whose structural formula is , m=0~5; the polyamine alkane is polyethyl polyamine, and its structural formula is , n=0~8.

[0016] More preferably, the silane coupling agent is coupling agent KH-550 or coupling agent G-570; the organic solvent is toluene; and the polyaminobenzene is benzene diamine, naphthalene-2,6-diamine or 2,4,6-quinazoline triamine.

[0017] Preferably, in step (3), the temperature of the reflux reaction is 100-200° C.; and the time of the reflux reaction is 2-10 h.

[0018] More preferably, the temperature of the reflux reaction is 100-120° C.; and the time of the reflux reaction is 5 h.

[0019] The second aspect of the present invention provides a modified composite nano plugging agent obtained by the above preparation method, wherein the modified composite nano plugging agent has nano iron particles as the core and is coated with silica, and the silica is grafted with long chains of phenyl polyamine; the particle size distribution of the modified composite nano plugging agent is between 30 and 150 nm.

[0020] The third aspect of the present invention provides the use of a modified composite nano plugging agent in oil field exploitation, wherein the modified composite nano plugging agent is added to the drilling fluid in a ratio of 0.1 to 0.5 wt %.

[0021] Beneficial effects of the present invention: (1) The modified composite nano plugging agent prepared by the present invention has an iron base as the core and a silicon dioxide composite sandwich, which improves the high temperature resistance. The silicon dioxide is modified and grafted with a long chain of phenyl polyamine, which improves the stability of the nanostructure, increases the material adsorption performance and salt resistance stability, and improves the plugging efficiency.

[0022] (2) The modified composite nano plugging agent prepared by the present invention has a particle size distribution of 30-120 nm, a small particle size and uniform distribution, can enter the tiny cracks in the well wall and effectively plug the cracks, and can be directly added to the drilling fluid for oil field exploitation. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 : Infrared spectrum of the water-based modified composite nano plugging agent prepared in Example 1; Figure 2 : Infrared spectrum of the water-based modified composite nano plugging agent prepared in Example 2; Figure 3 : Infrared spectrum of the water-based modified composite nano plugging agent prepared in Example 3; Figure 4 : Infrared spectrum of the water-based modified composite nano plugging agent prepared in Example 4; Figure 5 : Particle size distribution diagram of the water-based modified composite nano plugging agent prepared in Example 1; Figure 6 : TEM transmission electron microscope image of the water-based modified composite nano plugging agent prepared in Example 1; Figure 7 : Relative absorbance variation diagram of Examples 1-4 and Comparative Examples 1-3 samples. DETAILED DESCRIPTION

[0024] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0025] As introduced in the background technology section, the environment of oilfield exploitation is relatively complex. Whether it is the soil layer, water layer or drilling fluid of the oil well, there are a lot of sodium, calcium, magnesium and other ions, which will affect the salt resistance stability of the plugging agent, thereby affecting the plugging performance. The existing silica coupling agent not only has poor salt resistance stability, but also poor dispersibility in drilling fluid.

[0026] Based on this, the purpose of the present invention is to provide a water-based modified composite nano plugging agent and a preparation method thereof. The plugging agent prepared by the present invention has a structure as shown below: .

[0027] The plugging agent uses nano iron particles as the core. The nano iron particles have magnetism and can improve the salt resistance and stability of the plugging agent, and improve the dispersibility of the plugging agent. The nano iron particles are coated with silicon dioxide, so that the plugging agent can withstand high temperatures. The silicon dioxide is grafted with phenyl polyamine groups composed of polyaminobenzene, alkyl polyaldehyde and polyaminoalkane connected by chemical bonds. The grafted groups can improve the stability and dispersibility of the plugging agent in the drilling fluid, improve the plugging efficiency and reduce leakage.

[0028] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.

[0029] The test materials used in the examples of the present invention are all conventional test materials in the art and can be purchased through commercial channels.

[0030] Example 1 100g of lecithin and 40g of Tween were dissolved and dispersed in 40g of acetonitrile (500ml three-necked flask), 16g of ferroferric oxide (particle size 20nm) was evenly dispersed in 80g of deionized water, and then the iron source aqueous solution was slowly added dropwise to the acetonitrile, the temperature was raised to 60℃ and stirred for reaction for 2h to prepare an iron-based nanoemulsion.

[0031] 80 g of silicon dioxide (particle size 15 nm) was slowly added to the iron-based nanoemulsion, and then the three-necked flask was placed in a 20 kW ultrasonic device. After stirring for 1 hour, the reaction solution was placed in a high-speed centrifuge, centrifuged, and dried to obtain composite nanoparticles.

[0032] The composite nanoparticles (with a silica content of 50 g) and 10 g of coupling agent KH-550 were placed in a 2L three-necked flask, and then 250 g of toluene, followed by 306.7 g of diphenyl diamine (1.66 mol), 175 g of glutaraldehyde (1.75 mol), and 402.8 g of formic acid (8.75 mol) were added. The mixture was heated to 115 °C for reflux reaction for 5 h under nitrogen protection, and then 180.3 g of diethylenetriamine (1.75 mol) was added for further reflux reaction for 5 h. After the reaction, the solvent was removed by rotary evaporation, and then washed with dichloroethane and deionized water in turn. After filtering and drying, a water-based modified composite nano plugging agent was obtained. The particle size was measured by Malvern particle size analyzer to be 30-120 nm.

[0033] The water-based modified composite nano plugging agent prepared in Example 1 was slurried with anhydrous ethanol, filtered and dried to obtain an infrared spectrum (KBr tablet method). Figure 1 The curve in the figure shows that: 3313cm -1 、1603cm -1 Amino characteristic absorption peak: 2931cm -1 、1463cm -1 It is the characteristic absorption peak of methylene; 741cm -1 It is the absorption peak of substituted biphenyl.

[0034] The particle size distribution of the water-based modified composite nano plugging agent prepared in Example 1 is shown in Figure 5 It can be seen that the particle size is basically concentrated below 100nm, and the particle size distribution is relatively uniform. Figure 6 The TEM image also confirms this point, and it can be seen that the water-based modified composite nano plugging agent prepared in Example 1 is a coating structure.

[0035] Example 2 100 g of polyethylene glycol octylphenyl ether and 40 g of Tween were dissolved and dispersed in 40 g of acetone (500 ml three-necked flask), 16 g of ferroferric oxide (particle size 20 nm) was evenly dispersed in 80 g of deionized water, and then the iron source aqueous solution was slowly added dropwise to the acetone, the temperature was raised to 50 °C and stirred for reaction for 2 h to prepare an iron-based nanoemulsion.

[0036] 80 g of silicon dioxide (particle size 20 nm) was slowly added to the iron-based nanoemulsion, and then the three-necked flask was placed in a 30 kW ultrasonic device. After stirring for 1 hour, the reaction solution was placed in a high-speed centrifuge, centrifuged, and dried to obtain composite nanoparticles.

[0037] The composite nanoparticles (with a silica content of 50 g) and 10 g of coupling agent KH-550 were placed in a 2L three-necked flask, and then 250 g of toluene, followed by 263.4 g of naphthalene-2,6-diamine (1.66 mol), 273 g of 1,9-nonanedialdehyde (1.75 mol), and 402.8 g of formic acid (8.75 mol) were added. The mixture was heated to 115°C for reflux reaction for 5 h under nitrogen protection, and then 180.3 g of diethylenetriamine was added for further reflux reaction for 5 h. After the reaction was completed, the mixture was evaporated for desolventization, and then washed with dichloroethane and deionized water. After filtering and drying, a water-based modified composite nano plugging agent was obtained. The particle size was determined to be 50-100 nm using a Malvern particle size analyzer.

[0038] The water-based modified composite nano plugging agent prepared in Example 2 was slurried with anhydrous ethanol, filtered and dried to obtain an infrared spectrum (KBr tablet method). Figure 2 The curve in the figure shows that: 3352cm -1 、1606cm -1 Amino characteristic absorption peak: 2921cm -1 、1449cm -1 It is the characteristic absorption peak of methylene; 750cm -1 It is the absorption peak of substituted naphthalene.

[0039] Example 3 100 g of sodium stearate and 40 g of Tween were dissolved and dispersed in 40 g of acetonitrile (500 ml three-necked flask), 16 g of iron oxide (particle size 20 nm) was evenly dispersed in 80 g of deionized water, and then the iron source aqueous solution was slowly added dropwise to the acetonitrile, the temperature was raised to 60 ° C and stirred for reaction for 2 h to prepare an iron-based nanoemulsion.

[0040] 80 g of silicon dioxide (particle size 15 nm) was slowly added to the iron-based nanoemulsion, and then the three-necked flask was placed in a 30 kW ultrasonic device. After stirring for 1 hour, the reaction solution was placed in a high-speed centrifuge, centrifuged, and dried to obtain composite nanoparticles.

[0041] 50g of composite nanoparticles (so that the silica content is 50g) and 10g of coupling agent G-570 are placed in a 2L three-necked flask, and then 250g of toluene, followed by 291.6g of 2,4,6-quinazoline triamine (1.66mol), 175g of glutaraldehyde, and 402.8g of formic acid are added. The mixture is heated to 115°C for reflux reaction for 5h under nitrogen protection, and then 255.5g of triethylenetetramine (1.75mol) is added for further reflux reaction for 5h. After the reaction is completed, the mixture is evaporated for desolventization, and then washed with dichloroethane and deionized water. After filtering and drying, a water-based modified composite nano plugging agent is obtained. The particle size is 50~110nm determined by a Malvern particle size analyzer.

[0042] The water-based modified composite nano plugging agent prepared in Example 3 was slurried with anhydrous ethanol, filtered and dried to obtain an infrared spectrum (KBr tablet method). Figure 3 The curve in the figure shows that: 3311cm -1 、1604cm -1 Amino characteristic absorption peak; 2933cm -1 、1455cm -1 It is the characteristic absorption peak of methylene.

[0043] Example 4 100g of lecithin and 40g of Tween were dissolved and dispersed in 40g of acetone (500ml three-necked flask), 16g of ferroferric oxide (particle size 20nm) was evenly dispersed in 80g of deionized water, and then the iron source aqueous solution was slowly added dropwise to the acetone, the temperature was raised to 50℃ and stirred for reaction for 2h to prepare an iron-based nanoemulsion.

[0044] 80g of silicon dioxide (so that the silicon dioxide content is 50g) was slowly added to the iron-based nanoemulsion, and then the three-necked flask was placed in a 20kw ultrasonic device. After stirring for 1h, the reaction solution was placed in a high-speed centrifuge, centrifuged and dried to obtain composite nanoparticles. 50g of composite nanoparticles and 10g of coupling agent G-570 were placed in a 2L three-necked flask, and then 250g of toluene, followed by 291.6g of diphenyl diamine, 311.22g of adipaldehyde, and 402.8g of formic acid were added. The mixture was heated to 115°C for reflux reaction for 5h under nitrogen protection, and then 312.8g of hexaethylene heptamine was added for reflux reaction for 5h. After the reaction, the mixture was evaporated for desolventization, and then washed with dichloroethane and deionized water. After filtering and drying, a water-based modified composite nano plugging agent was obtained. The particle size was determined to be 40~100nm using a Malvern particle size analyzer.

[0045] The water-based modified composite nano plugging agent prepared in Example 4 was slurried with anhydrous ethanol, filtered and dried to obtain an infrared spectrum (KBr tablet method). Figure 4 The curve in the figure shows that: 3370cm -1 、1684cm -1 Amino characteristic absorption peak: 2921cm -1 、1457cm -1 It is the characteristic absorption peak of methylene.

[0046] Comparative Example 1 50g of silica (particle size 15nm) and 10g of coupling agent KH-550 were placed in a 2L three-necked flask, and then 250g of toluene, followed by 306.7g of diphenyl diamine (1.66mol), 175g of glutaraldehyde (1.75 mol), and 402.8g of formic acid (8.75mol) were added. The mixture was heated to 115°C for reflux reaction for 5h under nitrogen protection, and then 180.3g of diethylenetriamine (1.75mol) was added to continue reflux reaction for 5h. After the reaction, the solvent was removed by rotary evaporation, and then washed with dichloroethane and deionized water in turn. After filtering and drying, a composite nano plugging agent was obtained. The particle size was measured by Malvern particle size analyzer to be 30~105nm.

[0047] Comparative Example 2 100g of lecithin and 40g of Tween were dissolved and dispersed in 40g of acetonitrile (500ml three-necked flask), 16g of ferroferric oxide (particle size 20 nm) was evenly dispersed in 80g of deionized water, and then the iron source aqueous solution was slowly added dropwise to the acetonitrile, the temperature was raised to 60℃ and stirred for reaction for 2h to prepare an iron-based nanoemulsion.

[0048] 80 g of silicon dioxide (particle size 15 nm) was slowly added to the iron-based nanoemulsion, and then the three-necked flask was placed in a 20 kW ultrasonic device. After stirring for 1 hour, the reaction solution was placed in a high-speed centrifuge, centrifuged, and dried to obtain composite nanoparticles.

[0049] 50g of composite nanoparticles (with a silica content of 50g) and 10g of coupling agent KH-550 were placed in a 2L three-necked flask, and then 250g of toluene, 306.7g of diphenyl diamine (1.66mol) and 402.8g of formic acid (8.75mol) were added. The mixture was heated to 115°C for reflux reaction for 5h under nitrogen protection. After the reaction, the solvent was removed by rotary evaporation, and then washed with dichloroethane and deionized water in turn. After filtering and drying, a modified composite nano plugging agent was obtained. The particle size was measured by Malvern particle size analyzer to be 35~100nm.

[0050] Comparative Example 3 100g of lecithin and 40g of Tween were dissolved and dispersed in 40g of acetonitrile (500ml three-necked flask), 16g of ferroferric oxide (particle size 20nm) was evenly dispersed in 80g of deionized water, and then the iron source aqueous solution was slowly added dropwise to the acetonitrile, the temperature was raised to 60℃ and stirred for reaction for 2h to prepare an iron-based nanoemulsion.

[0051] 80 g of silicon dioxide (particle size 15 nm) was slowly added to the iron-based nanoemulsion, and then the three-necked flask was placed in a 20 kW ultrasonic device. After stirring for 1 hour, the reaction solution was placed in a high-speed centrifuge, centrifuged, and dried to obtain composite nanoparticles.

[0052] 50g of composite nanoparticles (so that the silica content is 50g) and 10g of coupling agent KH-550 are placed in a 2L three-necked flask, and then 250g of toluene, followed by 180.3g of diethylenetriamine (1.75 mol) and 402.8g of formic acid (8.75mol) are added. The mixture is heated to 115°C for reflux reaction for 5h under nitrogen protection. After the reaction, the solvent is removed by rotary evaporation, and then washed with dichloroethane and deionized water in turn. After filtering and drying, a modified composite nano plugging agent is obtained. The particle size is 30~110nm determined by a Malvern particle size analyzer.

[0053] Test Example 1 Under high-speed stirring, 16 parts of sodium bentonite were added to the water. After all the sodium bentonite was added, stirring was continued for 3 to 5 minutes. 0.64 parts of soda powder were added under stirring, and stirring was continued for 30 minutes until the slurry temperature was substantially close to room temperature to obtain a base slurry. 0.1wt%, 0.25wt%, and 0.5wt% of the plugging agents prepared in Examples 1 to 4 were added to the base slurry, respectively, aged at 150°C for 16h, placed in a high-temperature and high-pressure filter loss instrument, and a 50nm microporous filter membrane was used as a filter loss medium. The filter loss of each experimental slurry at 150°C and a pressure difference of 3.5MPa was tested, and the performance of the base slurry was determined. The results are shown in Table 1.

[0054] Table 1 Properties of base slurry It can be seen from Table 1 that as the amount of plugging agent increases, the apparent viscosity, plastic viscosity and dynamic shear force of the slurry gradually increase, while the filtration loss gradually decreases, but as the mass of the plugging agent increases, the reduction in filtration loss is not large. Taking all factors into consideration, the plugging agent prepared by adding 0.25 wt % of the embodiment is the best.

[0055] Test Example 2 (1) Outcrop cores were used to simulate nano-fracture formations. The average flow rate of the drilling fluid system in the outcrop cores was measured. The permeability of the outcrop cores before and after the addition of the plugging agent was calculated using the Darcy formula: K = QμL / (AΔP). The plugging rate of the plugging agent on the outcrop cores was then calculated using the plugging rate formula: (initial permeability - permeability after plugging) / initial permeability × 100% to evaluate its plugging performance.

[0056] (2) 0.25 wt % of the plugging agent prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was added to clean water, and then treated with 1 wt % of NaCl, 1 wt % of KCl, and 1 wt % of CaCl2 for 6 h. The plugging in step (1) was then performed, and the permeability after the salt solution treatment was tested. The results are shown in Table 2.

[0057] Table 2 Plugging performance evaluation According to Table 2, it can be seen that the plugging effect of Examples 1 to 4 is higher than that of Comparative Examples 1 to 3. Although the particle size ranges of the Examples and Comparative Examples are very close, and the plugging rates of the treatments of the groups are not much different; however, after being treated with salt solution, the increase in permeability of Examples 1 to 4 is lower than that of Comparative Examples 2 to 3, indicating that the selection of grafting materials affects salt resistance stability. The permeability of Comparative Example 1 is higher than that of Comparative Examples 2 to 3, indicating that nano iron particles have a significant effect on salt resistance stability.

[0058] Test Example 3 The base slurry was prepared according to the method of Experimental Example 1, and the plugging agents prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were added in an amount of 0.25% to obtain a water-based drilling fluid. The relative absorbance changes over time were shown in FIG. Figure 7 .

[0059] Relative absorbance = A1 / A0; A1 is the absorbance of the water-based drilling fluid at the maximum absorption wavelength on a certain day, and A0 is the absorbance of the water-based drilling fluid at the initial maximum absorption wavelength.

[0060] The smaller the change of relative absorbance over time, the more stable the water-based drilling fluid is. Figure 7 It can be seen that the relative absorbance changes of Examples 1 to 4 are significantly smaller than those of Comparative Examples 1 to 3 within 30 days after detection every 5 days, indicating that the blocking agent prepared by the present invention has good dispersibility. The dispersibility of Comparative Examples 2 and 3 is better than that of Comparative Example 1, and the dispersibility of Comparative Example 1 is the worst, indicating that the addition of the iron base helps to improve the dispersibility of the blocking agent.

[0061] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a water-based modified composite nano plugging agent, characterized in that: The following steps are involved: (1) adding a surfactant and an emulsifier to an organic solvent to obtain an emulsion, dispersing nano iron particles in deionized water to obtain a nano iron solution, slowly dropping the nano iron solution into the emulsion, heating and stirring to react, and obtaining an iron-based nano emulsion; (2) adding nano-silica to the iron-based nano-emulsion, ultrasonicating and stirring, centrifuging and drying to obtain composite nano-particles; (3) The composite nanoparticles and silane coupling agent are dispersed in an organic solvent, polyaminobenzene, alkyl polyaldehyde and formic acid are added, and the mixture is heated to reflux reaction under a protective atmosphere, and then the polyaminoalkane is added to continue the reflux reaction. After the reaction is completed, the reaction solution is spin-dried, and then washed, filtered and dried in sequence to obtain a modified composite nano plugging agent.

2. The preparation method according to claim 1, characterized in that: In step (1), the surfactant is polyethylene glycol octylphenyl ether, lecithin, cephalin, sodium dodecyl sulfate or sodium stearate; the emulsifier is Tween, Span or inositol phospholipids; the organic solvent is methanol, acetonitrile, ethanol, acetone or glycerol; the nano iron particles are ferroferric oxide, ferric oxide or ferric chloride; and the particle size of the nano iron particles is 10-30 nm.

3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the surfactant, the emulsifier and the organic solvent is 5:2:2; the mass ratio of the nano iron particles to deionized water is 1:5; and the mass ratio of the organic solution to deionized water is 1:

2.

4. The preparation method according to claim 1, characterized in that: In step (1), the heating temperature is 50-100° C.; and the stirring reaction time is 1-3 h.

5. The preparation method according to claim 1, characterized in that: In step (2), the particle size of the nano-silicon dioxide is 10-200 nm; the mass of the nano-silicon dioxide is 1-20 times the mass of the nano-iron particles; the power of the ultrasound is 10-50 kW; and the stirring time is 1-5 h.

6. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of silicon dioxide, silane coupling agent and organic solvent contained in the composite nanoparticles is 5:1:25; the molar ratio of polyaminobenzene, polyaminoalkane, alkyl polyaldehyde, formic acid and silicon dioxide contained in the composite nanoparticles is 2:2.1:2.1:10.5:

1.

7. The preparation method according to claim 1, characterized in that: In step (3), the silane coupling agent is selected from KH-590, KH-550, KH-560 or G-570; the organic solvent is selected from toluene, xylene, mesitylene, benzene or biphenyl; the polyaminobenzene is at least one of diphenyl diamine, o-phenylenediamine, 1,5-naphthalene diamine, naphthalene-2,6-diamine, anthracene-1,5-diamine, benzene-1,2,3-triamine or 2,4,6-quinazoline triamine; the alkyl polyaldehyde is a polyalkyl dialdehyde, and its structural formula is , m=0~5; the polyamine alkane is polyethyl polyamine, and its structural formula is , n=0~8.

8. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the reflux reaction is 100-200° C.; and the time of the reflux reaction is 2-10 h.

9. The modified composite nano plugging agent obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The modified composite nano plugging agent has nano iron particles as the core and is coated with silicon dioxide, on which long chains of phenyl polyamine are grafted; the particle size distribution of the modified composite nano plugging agent is between 30 and 150 nm.

10. The use of the modified composite nano plugging agent according to claim 9 in oil field exploitation, characterized in that: The modified composite nano plugging agent according to claim 9 is added to the drilling fluid in an amount of 0.1 to 0.5 wt %.

Citation Information

Patent Citations

  • Strong-adsorption salt-resistant blocking agent based on nano silicon dioxide and water-based drilling fluid

    CN114350331A

  • Temperature-resistant salt-resistant super-hydrophobic film-coated plugging agent and preparation method thereof

    CN114634802A